2017
DOI: 10.1186/s12960-017-0224-1
|View full text |Cite
|
Sign up to set email alerts
|

Cross-sectional description of nursing and midwifery pre-service education accreditation in east, central, and southern Africa in 2013

Abstract: BackgroundIn 2013, the World Health Organization issued guidelines, Transforming and Scaling Up Health Professional Education and Training, to improve the quality and relevance of health professional pre-service education. Central to these guidelines was establishing and strengthening education accreditation systems. To establish what current accreditation systems were for nursing and midwifery education and highlight areas for strengthening these systems, a study was undertaken to document the pre-service acc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 8 publications
(11 reference statements)
0
13
0
Order By: Relevance
“…The components also include well-trained teachers and a standardized curriculum supported by policy makers. Although accreditation, educational programmes and degree levels vary across countries (McCarthy et al, 2017), this paper focuses on the importance of development and implementation of a context-specific accreditation tool for midwifery education in Bangladesh.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The components also include well-trained teachers and a standardized curriculum supported by policy makers. Although accreditation, educational programmes and degree levels vary across countries (McCarthy et al, 2017), this paper focuses on the importance of development and implementation of a context-specific accreditation tool for midwifery education in Bangladesh.…”
Section: Discussionmentioning
confidence: 99%
“…According to McCarthy et al (2017), the process of accrediting midwifery education varies across countries, from self-assessment, to use of external inspectors, to use of an independent board to make accreditation decisions and/or provide feedback and recommendations to programmes. Within the climate of building a midwifery profession in Bangladesh (Bogren et al, 2015), and with country-specific knowledge gained through this process, it is recommended that Bangladesh Nursing and Midwifery Council should take the lead to commence the accreditation assessment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Once accredited by the relevant government agency, educational institutions can then exercise their power both to award degrees and to license and certify graduates for professional practice [11]. Given that fewer than half of all countries worldwide have an accreditation system in place for midwifery education [12,13], it will be difficult for any to argue that they offer quality education unless the educational programmes and institutions are accredited. As such, in 2017, the Bangladesh Government developed an accreditation assessment tool that involved local engagement.…”
Section: Introductionmentioning
confidence: 99%
“…For example, a 2013 survey of 70 nursing and midwifery professionals across East, Central, and Southern Africa revealed that many of the nursing and midwifery schools in these countries have limited materials and technical expertise. 5 As one 2014 study of 35 preservice schools in Tanzania concluded, “Pre-service FP [family planning] teaching in Tanzania is theoretical, poorly guided, and skewed toward short-acting methods; a majority of the schools are unable to produce competent FP service providers.” 6 …”
Section: Introductionmentioning
confidence: 99%